Art for Equality : The NAACP's Cultural Campaign for Civil Rights - Woodley, Jenny, 1980- (Book collections on Project MUSE., 2014)
"The National Association for the Advancement of Colored People (NAACP) is the nation's oldest civil rights organization, having dedicated itself to the fight for racial equality since 1909. While the group helped achieve substantial victories in the courtroom, the struggle for civil rights extended beyond gaining political support. It also required changing social attitudes. The NAACP thus worked to alter existing prejudices through the production of art that countered racist depictions of African Americans, focusing its efforts not only on changing the attitudes of the white middle class but also on encouraging racial pride and a sense of identity in the Black community. Art for Equality explores an important and little-studied side of the NAACP's activism in the cultural realm. In openly supporting African American artists, writers, and musicians in their creative endeavors, the organization aimed to change the way the public viewed the Black community. By overcoming stereotypes and the belief of the majority that African Americans were physically, intellectually, and morally inferior to whites, the NAACP believed it could begin to defeat racism. Illuminating important protests, from the fight against the 1915 film The Birth of a Nation to the production of anti-lynching art during the Harlem Renaissance, this insightful volume examines the successes and failures of the NAACP's cultural campaign from 1910 to the 1960s. Exploring the roles of gender and class in shaping the association's patronage of the arts, Art for Equality offers an in-depth analysis of the social and cultural climate during a time of radical change in America"--Provided by publisher.